Hysteroscopic myomectomy in a submucous fibroid 3 mm from the serosa: A case report - Case report from the endoscopy service of Ginendo-RJ - Lasmar, Ricardo Bassil; Barrozo, Paulo Roberto Mussel; Da Rosa, Daniela Baltar; Dias, Rogerio [UNESP] (Springer Nature, 2007)
This is a case report of a 39-year-old black woman, nulliparous, married who presented a heavy menstrual flow with clots and dysmenorrhea. Gynaecological examination of the uterus revealed RVF, mobility, no pain, slight enlargement, and right displacement. Magnetic resonance imaging (MRI) of the pelvis showed a 40 mm submucous fibroid with intramural component less than 50%, type 1, with a 3 mm distance from serosa. In an office hysteroscopy, it was noted a 40 mm submucous fibroid with an intramural component with less than 50%, type 1, classified in STEP-W submucous fibroids classification as a Score 6, Group II. The patient was submitted to partial hysteroscopic myomectomy, removing 60% of the fibroid volume in a 48.75-minute surgery. GnRH analogue was indicated for 3 months before another intervention. In the second evaluation MRI revealed a 22 mm-fibroid with intramural component more than 50%, type 2, with a 7 mm distance from serosa. Hysteroscopy found a 20 mm submucous fibroid, with intramural component more than 50%, type 2, Score 4, Group I on STEP-W classification. The patient was submitted to a second hysteroscopic myomectomy with complete removal and 10.5 minutes operating time, without complications. © 2006 Springer-Verlag.
Keywords: Hysteroscopic myomectomy; Hysteroscopy; Submucous fibroid; gonadorelin derivative; adult; case report; disease classification; drug indication; female; gynecological examination; human; hysteroscopy; myomectomy; nuclear magnetic resonance imaging; patient safety; second look surgery; serosa; surgical technique; treatment outcome; uterus myoma